Assisted Tandem Palladium(II)/Palladium(0)‐Catalyzed C‐ and N‐Arylations of Quinoxalin‐2(1 H)‐ones in Water. Issue 18 (6th November 2014) - Carrër, Amandine; Brion, Jean‐Daniel; Alami, Mouad; Messaoudi, Samir
Abstract A straightforward assisted tandem palladium(II)‐ and palladium(0)‐catalyzed direct C‐3 and N‐4 arylation of quinoxalin‐2(1 H)‐ones with boronic acids and aryl halides in water as safe and cheap solvent is reported. This environmentally friendly catalytic protocol is compatible with a wide range of functional groups and allows construction of various biologically important quinoxalin‐2(1 H)‐one backbones. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>